Assessment of the condition and possibilities of organic production in Poland - Tobiasz-Salach, Renata; Stadnik, Barbara (Polish Journal of Agronomy, 2021)
The article analyses the condition of organic farming in Poland on the basis of the data published by the Agricultural and Food Quality Inspection, the Central Statistical Office and available literature sources. The aim of the study was to assess the condition and prospects for the development of organic produc-tion in Poland. The results of the analysis indicate that there is a growing demand for organic products among consumers, which may contribute to the development of organic farming and an in-crease in the processing of organic products. However, in recent years, a decline in the number of organic farms and the total area of organic farming has been observed. Fodder plants, cereals as well as meadows and pastures are predominant in the structure of crops. Orchards, berries and vegetable cultivation as well as industrial crops are of lesser importance. Poultry, sheep and dairy cattle are predominant in organic livestock farming, whereas goats and cattle intended for meat account for a lower percentage. Among the organic agricultural products milk and dairy products are produced in the greatest quantities.